1993
DOI: 10.1056/nejm199311113292002
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Increase in Mortality among Patients with First Myocardial Infarctions Treated with Thrombolysis

Abstract: In patients with first myocardial infarctions who received thrombolytic therapy, age was a powerful independent predictor of both in-hospital and post-discharge mortality rates. The exponential, age-related increase in the mortality rate did not appear to be explained by larger infarcts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(86 citation statements)
references
References 16 publications
6
78
0
2
Order By: Relevance
“…Aging is associated with a progressive decline in physiological reserves that reduces the capacity for work (Chantler et al, 2006;Goldspink, 2005) and increases the susceptibility to injury (Abete et al, 1996;Juhaszova et al, 2005;Lesnefsky et al, 1994;Maggioni et al, 1993). A case in point is the myocardium, an aerobic tissue with high energy demands dependent on mitochondrial oxidative phosphorylation (OxPhos) where aging precipitates organ failure during stress.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is associated with a progressive decline in physiological reserves that reduces the capacity for work (Chantler et al, 2006;Goldspink, 2005) and increases the susceptibility to injury (Abete et al, 1996;Juhaszova et al, 2005;Lesnefsky et al, 1994;Maggioni et al, 1993). A case in point is the myocardium, an aerobic tissue with high energy demands dependent on mitochondrial oxidative phosphorylation (OxPhos) where aging precipitates organ failure during stress.…”
Section: Introductionmentioning
confidence: 99%
“…Other previous studies reported that mortality reaches ≥30% in octogenarian patients with AMI. 2,9,12) In this study, in-hospital mortality of the octogenarians with AMI was 19.9%. This suggests that emergent coronary angiography and subsequent intervention may be superior to thrombolysis and routine therapy with antiplatelet agents and heparin alone.…”
Section: Discussionmentioning
confidence: 54%
“…Previously reported reasons for increased mortality among elderly patients were multifactorial, including a high prevalence of comorbidity, 8,9) more diffuse multivessel disease, 4,8,10) delayed presentation, 11) greater risk of cardiac rupture, 12) insufficient use of beta-blocker 13) and aspirin, 14) and less aggressive treatment. 15) In this study, in-hospital mortality in the octogenarians with ACS was about three times higher than in the younger patients in spite of a similar rate of successful intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the risk stratification was performed 24 hours after the successful d-PCI and our results demonstrated that, for low risk patients, only very few combined untoward events occurred within 30 days after d-PCI. Previous studies [18][19][20][21] have demonstrated that serious complications, including death, usually occur within 48 hours after AMI. Therefore, it would be more appropriate to perform risk stratification at least 24 hours after d-PCI for patients with AMI in order to safely discharge patients earlier.…”
Section: Discussionmentioning
confidence: 99%